Beyond the fast–slow continuum: demographic dimensions structuring a tropical tree community. (9th May 2018) - Rüger, Nadja; Comita, Liza S.; Condit, Richard; Purves, Drew; Rosenbaum, Benjamin; Visser, Marco D.; Wright, S.J; Wirth, Christian
Abstract: Life‐history theory posits that trade‐offs between demographic rates constrain the range of viable life‐history strategies. For coexisting tropical tree species, the best established demographic trade‐off is the growth‐survival trade‐off. However, we know surprisingly little about co‐variation of growth and survival with measures of reproduction. We analysed demographic rates from seed to adult of 282 co‐occurring tropical tree and shrub species, including measures of reproduction and accounting for ontogeny. Besides the well‐established fast–slow continuum, we identified a second major dimension of demographic variation: a trade‐off between recruitment and seedling performance vs. growth and survival of larger individuals (≥ 1 cm dbh) corresponding to a 'stature–recruitment' axis. The two demographic dimensions were almost perfectly aligned with two independent trait dimensions (shade tolerance and size). Our results complement recent analyses of plant life‐history variation at the global scale and reveal that demographic trade‐offs along multiple axes act to structure local communities.